Rancang Bangun Kotak Pendingin Mini Portable Menggunakan Sumber Daya Listrik PLTS - M. Iqbal Baihaqi; Peri Setiyana; Rama Pirana; Vanri Gultom; Mohamad Sjahmanto (Universitas Pamulang, 2026)
Indonesia is located in the equatorial region and has abundant natural resources, including solar energy. Solar energy can be utilized as a power source for various applications, such as an electricity supply for beverage cooling systems. This study aims to design a solar power generation system to supply electrical energy for a beverage cooler. During sunny conditions, solar energy is directly used for cooling while simultaneously charging the battery. Meanwhile, during cloudy or rainy conditions, the stored energy in the battery is used as an alternative power source. The proposed system consists of solar panels, a solar charge controller, a battery, and an inverter. This system is expected to assist small-scale entrepreneurs in utilizing solar energy as a reliable power source for cooling beverages. Experimental results indicate an average temperature of 30.9°C, with a voltage of 15.29 V, a current of 3.26 A, and a maximum output power of 80.08 W, demonstrating the system's effectiveness. Abstrak: Indonesia terletak di kawasan khatulistiwa dan memiliki sumber daya alam yang melimpah, termasuk energi surya. Energi surya dapat dimanfaatkan sebagai sumber daya untuk berbagai aplikasi, seperti pasokan listrik bagi sistem pendingin minuman. Penelitian ini bertujuan untuk merancang sistem pembangkit listrik tenaga surya guna memasok energi listrik bagi pendingin minuman. Pada kondisi cerah, energi surya digunakan secara langsung untuk pendinginan sekaligus mengisi daya baterai. Sementara itu, pada kondisi mendung atau hujan, energi yang tersimpan dalam baterai digunakan sebagai sumber daya alternatif. Sistem yang diusulkan terdiri dari panel surya, pengatur pengisian daya surya (solar charge controller), baterai, dan inverter. Sistem ini dapat membantu pengusaha skala kecil dalam memanfaatkan energi surya sebagai sumber daya yang andal untuk mendinginkan minuman. Hasil eksperimen menunjukkan suhu rata-rata 30,9°C, dengan tegangan 15,29 V, arus 3,26 A, dan daya keluaran maksimum 80,08 W, yang menunjukkan keefektifan sistem.